Sistem Pendukung Keputusan Pemilihan Marketing Officer Terbaik dengan Metode Weighted Aggregated Sum Product Assesment (WASPAS) (Studi Kasus: Bank BRI Unit Simpang Marendal) - Dewi Anggraini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
PT. Bank Rakyat Indonesia (BRI) is one of the growing BUMN banks. Since its establishment BRI has played a role in advancing the nation and the State through its attention towards the development of small businesses, while continuing to run a modern banking business and be ready to compete. BRI's vision is